Kerentanan Petani Padi dan Gerakan Penolakan Terhadap Ekspansi Perkebunan Kelapa Sawit di Desa Rias, Kabupaten Bangka Selatan (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The expansion of oil palm plantations in close proximity to rice cultivation areas generates apprehension and concern regarding the well-being of paddy farmers in Rias Village. This condition further adds to the list of realities of vulnerability faced by the rice farmers there. This paper critically analyzes the forms of vulnerability and resistance movements demonstrated by Rias Village's paddy farmers against the expansion of oil palm plantations. This research employs a qualitative methodology utilizing a phenomenological approach. Data collection was executed through interviews, observations, literature reviews, and documentation. The findings of this study reveal that since the advent of oil palm expansion, the vulnerabilities experienced by paddy farmers have intensified across multiple dimensions: (1) Ecologically, manifested by an increase in the number and variety of pests detrimental to rice crops, and a reduction in the water availability within irrigation channels; (2) Economically, evident in the inflation of operational costs for paddy cultivation due to a heightened need for pesticides and pest control agents; and (3) Socially, characterized by a decline in trust (distrust) among farmers and farm laborers toward village and regional elites. Conversely, the form of resistance employed by the farmers against the pace of oil palm expansion utilizes a veiled or concealed resistance stance, which avoids direct acts of refusal in the presence of elite figures, instead employing cultural approaches and deliberation (consensus-building) with policymakers.